Periodic oscillation for an eight-neuron BAM neural network model with discrete delays - Feng, Chunhua (European Journal of Applied Sciences, 2021)
This paper investigates the existence of periodic oscillations for a eight-neuron BAM neural network model with discrete delays. Two theorems are provided to guarantee the existence of periodic oscillations for this model by using mathematical analysis method, which is simpler than bifurcation method. The criteria for selecting of the parameters in this network are provided. Computer simulation examples are presented to demonstrate the correctness of this method.